Conioscypha pruni sp. nov. (Conioscyphaceae, Conioscyphales), from sweet cherry (Prunus avium) from Sichuan Province, China - Liao, Yue-Chi; Deng, Li-Peng; Chen, Yan-Peng; Liu, Jian-Kui; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2025)
During our ongoing research on fungi associated with sweet cherries in Sichuan Province, China, we collected a saprophytic fungus that was identified as a species of Conioscypha based on ITS region sequence analysis and morphological characteristics. Further phylogenetic analysis based on the nuclear ribosomal internal transcribed spacer (ITS: ITS1-5.8S-ITS2), the nuclear ribosomal small subunit rRNA (SSU), the nuclear ribosomal large subunit rRNA (LSU), the partial translation elongation factor 1-alpha (TEF1), and the partial second largest subunit of RNA polymerase II (RPB2) confirmed that the collection represents a new species within the genus Conioscypha, and herein designated as C. pruni sp. nov. Phylogenetically, Conioscypha pruni forms a clade sister to C. minutispora. Morphologically, C. pruni differs from C. minutispora in having relatively larger conidia with dark-colored oil-drop-like inclusions. The study provided detailed descriptions, photographs of the new species, and an updated phylogeny for the genus Conioscypha.